VITAMIN D DAN DISFUNGSI ENDOTEL PADA KAKI DIABETIK - Raflis Raflis (Universitas Fort De Kock, 2021)
Globally the prevalence of type 2 Diabetes Mellitus (DM) among adult remain increase, including in Indonesia. DM with complicated condition might be cause disability that’s call diabetic foot. Diabetic foot is a leg disorder caused by uncontrolled diabetes mellitus resulting in blood vessel disorders, nervous disorders and infection. There are three main problems with diabetic foot, namely ischemia, neuropathy, and infection. These three problems, if triggered by trauma, will cause diabetic foot ulcers. Diabetic foot process initiated by their state of chronic hyperglycemia that causes inflammation in the arterial endothelium, cause endothelial dysfunction. Many studies that suggest a relationship of vitamin D with this inflammatory process. Hipovitaminosis state D will give effect to the increasing activity of the RAAS include hypertension, increased insulin resistance and dysfunction of pancreatic cells which can lead to hyperglycemia, decreased HDL and increased triglycerides. Hypovitaminosis vitamin D can directly increase the proinflammatory cytokines that produce TNF-α. This inflammatory process would lead to decreased levels of Nitric Oxide (NO) and increased ROS. Vitamin D might be have a role in cotrolling inflammation in endothelial cells among people with diabetic foot.Keywords: endothelial dysfunction, diabetic foot, vitamin D